Leukemic Transdifferentiation of Follicular Lymphoma Into an Acute Histiocytic Leukemia in a 52-Year-Old Caucasian Woman. Issue 2 (11th April 2016) - Steussy, Bryan; Lekostaj, Jacqueline; Qian, Qining; Rosenthal, Nancy; Holman, Carol J.; Syrbu, Sergei; Darbro, Benjamin; Bossler, Aaron; Karandikar, Nitin J.
Abstract : We report an instructive case of acute myeloid leukemia with histiocytic differentiation ( acute histiocytic leukemia ) arising in a patient, a 52-year-old woman with a history of follicular lymphoma. The results of genetic studies proved a clonal relationship between the lymphoma and the leukemic cells. To our knowledge, this is the first report of leukemic transdifferentiation of follicular lymphoma into modified base 5-methylcytosine (M 5 c)–like acute histiocytic leukemia and the first reported karyotype on a transdifferentiated neoplasm.